Study of the influence of changes in the motor speed on the technological characteristics of a feed pellet mill - Ramsh, V.; Kondrat, O. (Energy and Automation, 2025)
The influence of changes in the motor speed on the pellet mill performance, as well as on the technological and energy parameters of feed pellet mills is investigated. The dependencies between the motor speed and such indicators as productivity and general characteristics of the equipment operation are revealed. Productivity increases with increasing speed up to a certain point, but for most feeds, there is a stabilisation or even a decrease in productivity after reaching the maximum level. Different feeds have their own optimal characteristics: soybeans and a mixture of cereals are better suited for pellet mills due to their higher productivity, while barley has a much lower productivity, so it is necessary to make adjustments to the technological process (change the structure, moisture content or other parameters).Feed moisture content in the range of 9-9.6% contributes to high productivity, while barley has the lowest productivity even at optimal moisture content, which may be due to its physical properties.The research allows us to determine the optimal operating modes of the pellet mill, which achieve the production of high-quality feed with minimal energy consumption.Further research can be aimed at studying the influence of other parameters, such as temperature and the addition of various components.Deviations in the change in the motor speed lead to a disruption in the stable flow of technological processes, a decrease in product quality, a reduction in the service life of electrical equipment, an increase in electricity losses in power consumption systems, and the creation of emergencies that can threaten human safety [1].Key words: feed pellet mill, electric drive, performance, frequency converter, network analyser